Pengaruh Current Ratio (CR), Return On Equity (ROE), Debt to Equity Ratio (DER) dan Net Profit Margin (NPM) Terhadap Harga Saham Perusahaan (Studi Empiris Pada Perusahaan LQ 45 Yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Salsabila, Sekar Salma; , Drs. Eko Sugiyanto, M. Si (2017)
This study aims to find the effect of Current Ratio (CR), Return On Equity (ROE), Debt to Equity Ratio (DER) and Net Profit Margin (NPM) on Stock Price of the LQ 45 Company listed in Indonesian Stock Exchange in 2013 to 2015. The stock price is the present value of the income received by investors in the future that occur as a result of supply and demand in the capital market. The population used in this study is all LQ 45 Company listed in Indonesian Stock Exchange in 2013 to 2015. This study use purposive sampling technique with predetermined criteria. The sample used 57 companies. Analysis technique used in multiple regression analysis. The result of this study shows that just Return On Equity (ROE) variable have significant effect on stock price. While Current Ratio (CR), Debt to Equity Ratio (DER) dan Net Profit Margin (NPM) variable has no significant on stock price.